Experimental investigation on sorption enhanced gasification (SEG) of biomass in a fluidized bed reactor for producing a tailored syngas. (1st January 2020) - Martínez, I.; Kulakova, V.; Grasa, G.; Murillo, R.
Abstract: Synthetic fuel production from renewable energy sources like biomass is gaining importance driven by the ambitious targets for reducing greenhouse gas emissions worldwide. Sorption enhanced gasification (SEG) proposes carrying out the gasification of biomass in the presence of a CO2 sorbent, which allows producing a syngas with a suitable composition for a subsequent synthetic fuel production step. This study aims at analysing the effect of different operating parameters (e.g. steam-to-carbon (S/C) ratio, CO2 sorption capacity and sorbent-to-biomass ratio) in the syngas composition and char conversion obtained in a 30 kWth bubbling fluidized bed gasifier, using grape seeds as feedstock. The importance of reducing the formation of higher hydrocarbons through a high steam-to-carbon ratio and using a CO2 sorbent with high sorption capacity is assessed. C3 -C4 and unsaturated C2 hydrocarbons contents below 1%vol. (in dry and N2 free basis) can be achieved when working with S/C ratios of 1.5 at gasification temperatures from 700 to 740 °C. Varying the amount of the CO2 separated in the gasifier (by modifying the temperature or the CO2 sorption capacity of the sorbent) the content of H2, CO and CO2 in the syngas produced can be greatly modified, resulting in a module M = (H2 -CO2 )/(CO + CO2 ) that ranges from 1.2 to almost 3.